2013
DOI: 10.1177/0892705713505611
|View full text |Cite
|
Sign up to set email alerts
|

Processing characteristics and mechanical and electrical properties of chlorinated styrene–butadiene rubber/fly ash composites

Abstract: This work focused on the utilization of waste fly ash (FA) as filler in the reinforcement of chlorinated styrene-butadiene rubber (CSBR) with reference to their processing characteristics, morphological, thermal, and mechanical properties, solvent resistance, and electrical resistivity measurements. Rheometric properties such as optimum cure time and scorch time decreases with increase in filler content, whereas maximum torque increases up to 30 phr for FA particles. An appreciable increase in glass transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 36 publications
(33 reference statements)
1
17
0
Order By: Relevance
“…6b, c, it can be observed that T g and T m of PBMA nanocomposite constantly increased with increase in the concentration of nanoparticles. Several researchers suggest that the addition of nanoparticles into the polymer matrix leads to strong interfacial bonding between the polymer chain and the nanoparticle surfaces and therefore the interfacial layer affects the glass transition temperature of the polymer matrix [21]. In the present study, nanocomposites are synthesised by in situ polymerisation process, where the monomers are first absorbed on the surface of TiO 2 nanoparticles.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…6b, c, it can be observed that T g and T m of PBMA nanocomposite constantly increased with increase in the concentration of nanoparticles. Several researchers suggest that the addition of nanoparticles into the polymer matrix leads to strong interfacial bonding between the polymer chain and the nanoparticle surfaces and therefore the interfacial layer affects the glass transition temperature of the polymer matrix [21]. In the present study, nanocomposites are synthesised by in situ polymerisation process, where the monomers are first absorbed on the surface of TiO 2 nanoparticles.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…In the past, polymer blending has been used for improving electrical and mechanical properties of polymer films in various applications [23][24][25][26][27][28][29][30][31][32][33][34][35][36]. The production of petroleum-based polymers and their utilization has increased significantly.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Research in the field of such polymer mainly focused on the modification of existing polymers, so that their visibility can further be improved. One of the successful approaches has been preparing the composite polymer network containing different metal oxide nanoparticles such as Fe 3 O 4 , MnWO 4 , TiO 2 , and fly ash composites . Among these, magnetite (Fe 3 O 4 )‐based polymer composites have attracted considerable attention especially in the field of polymer chemistry and physics because of their various applications such as magnetic recording media, photonic crystallites, sensors, and actuators.…”
Section: Introductionmentioning
confidence: 99%